Workers' voice in the 100 largest European companies - Anke Hassel; Nicole Helmerich (Hans-Böckler-Stiftung, 2017)
Workers' Voice is widely present among the largest 100 firms in Europe. 90 % of the largest firms participate in collective bargaining (CBA), 73 % have a European Works Council (EWC) and 44 % have Board-Level Employee Representation (BLER). 27 % have a European Company Agreement (ECA), and 23 % an International Framework Agreement (IFA). The data set allows three broad conclusions: - First, Workers' Voice is mostly cumulative. Companieswith BLER always participate in collective bargaining and generally have a higher percentage of other forms of Workers' Voice in place than companies without BLER. Companies with BLER and CBA in place also almost always have at least one European Works Council in place and, in 40.9 % of the firms, also at least one European Company Agreement.- Second, Board-Level Employee Representation and collective bargaining seem to strengthen good corporate governance. Companies with BLER offered considerably lower remuneration packages within the company than companies without BLER. Companies without BLER as well as companies without CBA spent, on average, significantly more money on the highest remuneration packages than companies with BLER andCBA present and companies with only CBA present. Companies with BLER are associated with a lower influence of a single biggest owner.- Third, companies with strong Workers' Voice show better performance compared to those without. Companies with both BLER and CBA have higher market value as well as higher net sales.
Keywords: 330